A PATIENT-CENTRIC SIX-SIGMA DECISION SUPPORT SYSTEM FRAMEWORK FOR CONTINUOUS QUALITY IMPROVEMENT IN CLINICS - Hlongwane, Sanelisiwe; Ngongoni, Chipo; Grobbelaar, Sara S (Saartjie) (The South African Journal of Industrial Engineering, 2019)
Primary health care facilities are widely regarded as the backbone of the South African healthcare system. For this reason, formalised standards such as the ‘ideal clinic’ and ‘national core standards’ dictate expected service levels for clinics. Although this is a big step towards the improvement of service delivery at the facilities, the level of uptake of and adherence to these standards is concerning. Service quality plays a huge role in the level of patient satisfaction, and emphasis is placed on the features of quality that are of importance to the patient. To this end, the focus on the patient is an important dimension in healthcare quality management in order to improve the service quality in healthcare facilities. This article provides an overview of quality and how it is managed in the context of clinics in South Africa. It outlines the gaps, aligned with how well quality is managed, from a patient perspective. The paper proposes a decision support framework aimed at continuous improvement of quality in clinics. The tool was developed using the Six Sigma methodology, complemented by service quality assessment instruments. The structure of the tool provides an integrated systematic approach that can assist the healthcare decision-maker in tracking the continuous improvement of processes and activities in clinics. The tool also takes the first step towards digitising a typical paper-based system.